A Qualitative Study On Socio-Economic Implications Of Ecotourism In District Swat, KP: Perspectives From The Community - Ali, Zahid; Nasir, Muhammad Jamal; Iqbal, Shahid (Migration Letters, 2024)
Tourism has the capacity to transform the economic landscape, benefiting both developed and developing countries. While tourism can boost economic growth and provide numerous advantages to local communities, it also has negative implications such as traffic congestion, overcrowding, increased crime rates, and environmental degradation, which frequently upset local norms and culture. The purpose of this study is to look into the local community’s perspectives of tourism’s socioeconomic, environmental, and cultural impacts in Swat, Khyber Pakhtunkhwa, Pakistan. It also tries to examine the extent of community involvement in tourism development. The study illustrates that tourism activities in Swat improve the economic situation of local residents based on primary data collected from 305 respondents via surveys and secondary data. However, they hurt the region’s natural environment and upset local conventions and cultures. The study suggests that the local government encourages community engagement in processes decision-making to improve residents’ quality of life. Furthermore, it encourages tourists to avoid immoral behaviors that could undermine local customs and traditions. Furthermore, the study proposes improving collaboration and friendliness among residents to boost recurrent tourism visits.